Feasibility of implementing formal long-distance mentorship for public health physicians: a case study of Association of Public Health Physicians of Nigeria - Uche Shalom Obi; Chinyere Mbachu; Benjamin S. C. Uzochukwu (BMC, 2021)
Abstract Background Conflicting schedules and geographic access limit prospects for mutually beneficial relationships between experts and early career professionals. A formal long-distance mentorship program could address these barriers and potentially bridge the gap of traditional face-to-face mentorship. This study was done to determine the feasibility of implementing a formal long-distance mentorship program amongst public health physicians of Nigeria. Method A mixed-method study comprising of in-depth interviews and surveys was used to collect information from members of the Association of Public Health Physicians in Nigeria. A total of 134 survey participants were recruited consecutively during an annual scientific meeting of the association. In-depth interviewees were purposively selected to ensure diversity in expertise, experience, and social stratifiers such as age. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic content analysis. Results Public health physicians of Nigeria are willing to participate in a formal Long-Distance Mentorship Program, and four elements of feasibility were highlighted as necessary for implementing the program. Namely i) capacity to coordinate LDMP, ii) technical expertise and individual competence to provide mentorship, iii) financial capacity to implement and sustain LDMP, and iv) demand for mentorship by mentees. There is a consensus that the organizational structure of the National Postgraduate Medical College of Nigeria and West African College of Physicians provide an enabling environment to initiate a LDMP for public health physicians of Nigeria. The vast human resources with various expertise and the annual National conferences can be leveraged upon to champion and administer the program. However, there is a need for an administrative structure and technical expertise to enable proper coordination. More so, the need for demand creation and the financial requirement was considered gaps that need to be filled to be able to ensure feasibility. Bivariate analysis showed a significant relationship between the dependent variable (preferred role- mentor/mentee) and independent variables (age, year of graduation, and the number of years of practice), while the binary logistic regression model showed that physicians are more likely to participate as mentors with each unit increase in the number of years of practice. This further buttressed the need to commence the mentoring process as soon as trainees gain entrance into the program, as mentorship does not just prepare them for excellent public health practice, but also builds their capacity to mentor the younger and upcoming public health physicians. Conclusion There are enabling structures to incorporate a formal long-distance mentorship program for public health physicians in Nigeria, and physicians are willing to participate in such a program. However, the feasibility of establishing a successful and sustainable program will require robust coordination, technical expertise, demand creation, and financial commitment at both institutional and college levels.